The Patient's Perception of the role of Prayer in the Family Practice Consultation - A.S. Liddle (South African Family Practice)
This study aims for a deeper understanding of patients' views on prayer in the family practice consultation. Family practice patients have diverse religious beliefs and practices. Relating religion to medicine is, on the one hand, considered an unusual occurrence, and a sensitive almost taboo subject. On the other hand, religion is considered to form an integral part of medicine, not only by divine authority but by virtue of factual knowledge and reason. Reticence, to research prayer, based on the potential of divine punitive reaction is rejected since it confuses the spiritual action of prayer with its consequences. Lay press articles, books written by doctors and medical publications have brought these issues under the spotlight. A review of the literature (PRE- 1995), reveals two studies, which assessed patients' expectation of prayer and discussion of religion.